Dietary patterns and fatigue in female slimmers. Issue 6 (29th May 2020) - Kaya Kaçar, Hüsna; Avery, Amanda; Bennett, Sarah; McCullough, Fiona
Abstract : Purpose: This paper aims to understand the association of dietary patterns with perceived fatigue and identify predictors for presence of fatigue in women who are obese and trying to lose weight. Design/methodology/approach: An online survey, hosted by slimming world (SW), comprised of a questionnaire regarding weight, level of fatigue and food frequency questionnaire before joining the weight management programme (T0) and current data (T1) was conducted. In total, 543 non-pregnant women with obesity of child-bearing age (19-49 years) completed the survey (T0-T1). The principal components analysis was used to determine dietary patterns and multinomial logistic regression was used to analyse predictors for presence of fatigue. Findings: The participants who have a "simple carbohydrate and high fat" dietary pattern were more likely to have fatigue at T0 ( p  ≤ 0.001) and those who followed a "vegetables" dietary pattern were less likely to have fatigue at T1 ( p  ≤ 0.05). The study findings indicate that while "simple carbohydrate and high fat" dietary pattern was associated with increased risk of fatigue, "vegetables" dietary pattern was associated with reduced risk of fatigue and a higher percentage of weight loss. Originality/value: The present study appears to be the first study to examine associations between dietary patterns and fatigue. The strengths of the study included the in-depth analysis of this association in both before joining a weight management programme (SW) and currently as a member of SW with an adequate sample size.